State governance and technological innovation in emerging economies: State-owned enterprise restructuration and institutional logic dissonance in China’s high-speed train sector - Genin, Aurora Liu; Tan, Justin; Song, Juan (Journal of International Business Studies, 2021)
Can state governance spur firm innovation in an emerging economy and transform state-owned enterprises (SOEs) from “dying dinosaurs” to “dynamic dynamos”? We seek an answer to this question by investigating the innovative performance of restructured SOEs in China’s high-speed train sector. We expect that SOE restructuration will improve firm innovation, but that the degree of improvement will depend on how the state conducts firm governance. Building on institutional theory, we distinguish state governance via equity ownership and administrative affiliation in an emerging economy with market-hierarchy institutional conflicts. Under such conflicts, restructured SOEs experience institutional logic dissonance, which hinders organizational change for technological innovation. We hypothesize that state ownership exacerbates institutional logic dissonance at a restructured SOE, thus limiting innovation improvement from restructuration; in contrast, state affiliation mitigates firm dissonance and hence augments such improvement. We find empirical evidence for these hypotheses in a comprehensive panel of high-speed train manufacturers in China between 1989 and 2015. This study contributes to the institution-based theory of technological innovation in emerging economies. On the practical front, our findings suggest that emerging states may adopt arms-length governance to spur SOE innovation and unleash these dynamic dynamos to fuel sustainable economic growth.